Probiotics and paraprobiotics in aquaculture: a sustainable strategy for enhancing fish growth, health and disease prevention-a review - Fachri, Muhammad; Amoah, Kwaku; Huang, Yu; Cai, Jia; Alfatat, Alma; Ndandala, Charles Brighton; Shija, Vicent Michael; Jin, Xiao; Bissih, Fred; Chen, Huapu (Frontiers in Marine Science, 2024)
This review delves into the increasing interest in probiotics and paraprobiotics as a viable alternative to antibiotics in aquaculture, highlighting their potential to enhance fish health and prevent diseases. As the aquaculture industry continues its global expansion, addressing the challenges associated with disease outbreaks in high-density fish populations becomes imperative. The review underscores the promising role of probiotics and paraprobiotics as a sustainable strategy to mitigate these challenges. The diverse positive impacts of various probiotic strains such as Arthrobacter, Bifidobacteria, Bacillus, Lactobacillus, Bifidobacterium, Clostridium, and others emphasize their roles in enhancing growth, resistance to diseases (including bacterial, viral, and parasitic infections), stress reduction, water quality management, and environmental sustainability. Challenges such as stability, host specificity, and regulatory considerations must be addressed to optimize the use of probiotics in aquaculture. Additionally, paraprobiotics, or non-viable microbial cells, present a safer alternative to the criticized antibiotics and even live probiotics in environments where microbial viability poses a risk. These inactivated cells retain the ability to modulate the immune system and improve gut health, offering a promising complementary approach to fish disease prevention. The review advocates for a systematic approach combining research, innovation, and collaboration to effectively integrate probiotics and paraprobiotics into fish farming practices. Furthermore, the mechanisms by which probiotics and paraprobiotics modulate gut microbiota, produce antimicrobial compounds, and strengthen fish's immune system have been elucidated. Moreover, the practical applications of probiotics in fish farming, including optimal administration methods and the challenges and limitations faced by the industry, have been discussed. Emphasis on the importance of continued research to explore new probiotic and paraprobiotic strains and develop innovative delivery systems to ensure the sustainability of aquaculture has been discussed. By enhancing fish health, reducing the need for antibiotics, and improving water quality, probiotics, and paraprobiotics contribute to more sustainable and environmentally responsible aquaculture operations.